Multicolor Fluorescence In Situ Hybridization (FISH) Approaches for Simultaneous Analysis of the Entire Human Genome. (14th September 2018) - Zhang, Chengsheng; Cerveira, Eliza; Rens, Willem; Yang, Fengtang; Lee, Charles
Abstract: Analysis of the organization of the human genome is vital for understanding genetic diversity, human evolution, and disease pathogenesis. A number of approaches, such as multicolor fluorescence in situ hybridization (FISH) assays, cytogenomic microarray (CMA), and next‐generation sequencing (NGS) technologies, are available for simultaneous analysis of the entire human genome. Multicolor FISH‐based spectral karyotyping (SKY), multiplex FISH (M‐FISH), and Rx‐FISH may provide rapid identification of interchromosomal and intrachromosomal rearrangements as well as the origin of unidentified extrachromosomal elements. Recent advances in molecular cytogenetics have made it possible to efficiently examine the entire human genome in a single experiment at much higher resolution and specificity using CMA and NGS technologies. Here, we present an overview of the approaches available for genome‐wide analyses. © 2018 by John Wiley & Sons, Inc.